Emblems of Eloquence : Opera and Women's Voices in Seventeenth-Century Venice - Heller, Wendy, 1955- (Book collections on Project MUSE., 2003)
Drawing upon a complex web of early modern sources and ancient texts, this engaging study is a comprehensive treatment of women, gender, and sexuality in 17th-century opera.